(3GdJMOjGJ GdJi JhGLg GdLgGR GdeUQai hWQb ehGLgJgG (B: s (3eY GdJWHjb Ydi GdMGdI GdeUQjI (B2000- 2010 / s - (3QMGH MSjf YeGQs; (3SGei GdSjO (B: s ((3GdbGgQI (B: s (3QMGH MSjf YeGQ (B: s, 2012)
(3dbO NdUfG ef gPg GdQSGdI Gdi Gf GdbWGY GdeUQai jYO GMO GcKQ GdbWGYGJ GdGbJUGOjI GdeSJLjHI ddJZjQGJ GdeMdjI hGdOhdjI hdYd Gge gPg GdJZjQGJ GdJWhQ GdJcfhdhLi GdJMQQ ef GdbjhO GdJi JYjb JLGQI GdNOeGJ GdeUQajI gPG HGdEVGaI Gdi XghQ cjGfGJ eUQajI YedGbI hbO JHGjfJ GdGReGJ GdeUQajI GdJi TgOgG GdYGde NdGd GdYbOjf GdeGVjjf MjK GJLGg GdGbJUGOjGJ GdeJbOeI HNWhGJ HYjOI fMh GdJMQQ hGdGfaJGM hGdefGaSI hYdi eSJhi GdGbJUGO GdeUQi abO hGLgJ GdHfhc GdeUQjI hHNGUI Hfhc GdbWGY GdYGe Ydi GYJHGQ GfgG JSJMhP Ydi fSHI cHjQI ef MLe GdShb GdeUQai GdeUQi GdYOjO ef GdJMOjGJ GdJi GfYcSJ YdjgG ef GdfXGe GdeUQai GdYGdeis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdGbJUGO hGdYdhe GdSjGSjI (B- (3bSe GdGbJUGOs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdYhdeI s; (3GdbWGY GdeUQai s; (3NUNUI GdHfhc s